Islamic Religious Education in the Era of Revolution 4.0 (Descriptive Study of Bondowoso 2 Public High School) - Yamin, Mohamad; Yusuf, Lucky Damara (Universitas Syiah Kuala, 2025)
Disruptive innovation presents many innovations without established organizations realizing it but is felt to be disrupting the activities of the old system order and destroying the current system. This has an impact that is not simple. It impacts all aspects of human life. Included in this is education. Putting on a competition literation on every semester.Providing reading park.Providing class library.make library as central activity.Putting on a literation activity based on 4.0. Evolution is done once a week that is Meeting Teachers Subject (MGMP) Study of Bondowoso 2 Public High School). This type of experiment use approach qualitive with the deskriptif type.Experiment done in Study of Bondowoso 2 Public High School). The indikator Literation Education of Islamic Religion of student in Study of Bondowoso 2 Public High School)High School Surabaya in the era 4.0 is that; Know and knowing all the book that was recommend by school. Writing seriously and evaluating in a manner of critical from the writing that is made and giving mean for teks that ias read and made can show the literation activities that can be accsess in a manner of communal (in a manner of wide Effort of teacher Education Islamic Religion to improve Literation Education Islamic Religion student from in Study of Bondowoso 2 Public High School) in the Era 4.0 is: Entering literation to the subjects trough Plan Implementation Studying. Reading 15 minutes before KBM startedKeywords: Religious Education, The Era of Revolution 4.0, Study of Bondowoso 2 Public High School